A novel method for establishing solutions to non-linear ordinary differential equations - Horak, Vladimir (2018)
The paper presents a novel method that allows one to establish solutions of some non-linear ordinary differential equations, which contain products of the unknown functions and/or its derivatives. This method can be especially useful when one needs to address the problem of the solution existence for such equations. In particular, the method was used in this work for illustrative purposes, to find some solutions to the Blasius equation.